Family quality of life of parents of children with intellectual disability: Do psychological stress and parental involvement matter? - Cheng, Sanyin; Li, Jiaqi; Li, Qiaoqiao; Li, Xuxu; Luo, Yan (Journal of intellectual disabilities, 2025)
The psychological stress of parents and improving family quality of life (FQoL) are continuing concerns for families of children with intellectual disability. We need to identify further ways to reduce their stress and improve their FQoL in China. Examine the interrelations between psychological stress, parental involvement, and FQoL for parents with intellectual disability in mainland China. Four hundred sixty seven parents of children with intellectual disability completed instruments measuring variables. Structural equation modelling (SEM) was employed to examine the interrelations. Psychological stress, directly and indirectly, influenced parental involvement in FQoL. Physical and mental response (PMR) and risk awareness (RA) had a positive direct effect on FQoL, and optimistic hope (OH) had a negative effect on FQoL. Psychological stress affects FQoL of parents with children with intellectual disability in complex ways. Policies should be developed to help parents with children with disability decrease stress and develop scientific parental involvement.